"The Disastrous adventures" pedagogical narrative schemas - Charnay, Thierry (Ondina - Ondine, 2020)
It is a question of emphasizing the harmful effect of the narrative schemas on both the reflection and the intellectual formation of the pupils and the students who constantly invoke them, especially when it comes to studying a story. The doxa imposes the anonymized use of two diagrams used separately, the quinary schema of P. Larivaille and the actantial schema/model of Greimas, which are almost exclusively intended for quest narratives. We will show that not only other schemes are more powerful and more efficient, but that research has not yet, far from it, explored other patterns corresponding to other types of narratives, such as those of flight, risk, degradation, etc. Key words: narrative schemas, quinary schema, actantial schema, hypothetical representations, quest, storytelling.